Investigation of structural, dynamical, electronic and magnetic properties of MX2(M = Mo, X = Se, Te) materials - Khanal, Kamal; Pokharel, Arpan; Neupane, Tejendra; Yadav, Sukrit Kumar; Aryal, Nabin; Rijal, Om Shree; Neupane, Hari Krishna (Scientific World, 2025)
Two-dimensional (2D) transition metal dichalcogenides (TMDCs) materials have potential applications in the field of device applications. In the present work, we explored the structural, dynamical, electronic, and magnetic properties of MoSe2 and MoTe2 TMDCs materials by using density functional theory (DFT) method. For the investigation of material’s structural and dynamical stability, we have estimated their ground state energies, bond length of atoms presented in the structures, and phonon dispersion curves respectively. They are found to be structurally and dynamically stable materials. Furthermore, we have studied the electronic and magnetic properties of MoSe2 and MoTe2 materials. Electronic properties are investigated by the analysis of their band structure, and density of states (DOS) plots. Both the materials are found to be small band gap p-type semiconductor. For the investigation of material’s magnetic properties, we have interpretated the DOS and partial density of states (PDOS) plots. In both plots, up-and down-spin states are symmetrically distributed around the Fermi energy level. They reveal that MoSe2 and MoTe2 have non-magnetic properties. Based on the multi-properties investigation of MoSe2 and MoTe2, they can be used in a variety of device applications, including optoelectronic, semiconducting, energy storage, and sensing devices.